2017
DOI: 10.1177/1098612x17706799
|View full text |Cite
|
Sign up to set email alerts
|

Clinical topographical anatomy of the gastro-oesophageal junction in the cat

Abstract: Objectives The purpose of the present study was to describe histologically the gastro-oesophageal junction in the cat and interrelationships of this region. Our hypothesis was that cats are devoid of abdominal oesophagus. Methods Three centimetres of the terminal oesophagus, the phreno-oesophageal membrane with 1-2 cm margins of the diaphragmatic crural muscle and the proximal 3 cm of the gastric cardia were obtained from nine domestic shorthair cats and one domestic longhair cat that were euthanased for reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The whole oesophagus, inclusive of the caudal oesophageal sphincter, is situated within the thoracic cavity rather than the abdominal cavity. This may suggest that in this report, the stricture is located extraluminal to the cardia of the stomach as opposed to an extraluminal caudal oesophageal stricture 15…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The whole oesophagus, inclusive of the caudal oesophageal sphincter, is situated within the thoracic cavity rather than the abdominal cavity. This may suggest that in this report, the stricture is located extraluminal to the cardia of the stomach as opposed to an extraluminal caudal oesophageal stricture 15…”
Section: Discussionmentioning
confidence: 61%
“…This may suggest that in this report, the stricture is located extraluminal to the cardia of the stomach as opposed to an extraluminal caudal oesophageal stricture. 15 Several studies have described the closure of diaphragmatic hernias with the emphasis being on: (i) closure in a dorsal to ventral direction allowing the surgeon greatest exposure and (ii) avoidance of an excessively tight closure, lowering the likelihood of necrosis of the repaired tissue and/or overt tension leading to breakdown. 7 Both non-absorbable and absorbable suture materials have been used and there is little evidence to support the use of one over the other.…”
Section: Discussionmentioning
confidence: 99%
“…The phrenoesophageal membrane, with its ascending and descending limb, is the ligament that connects the esophagus to the diaphragm, with the descending limb being connected to the stomach just below the gastroesophageal junction [ 29 ]. However, Voutsinou et al reported the absence of abdominal esophagus in nine domestic shorthaired cats and one domestic longhaired cat, with the zone of mucosa transition being detected between the bifurcation of the diaphragm and the phrenoesophageal membrane [ 30 ]. The gastroesophageal junction is also surgically important during the localization of the gastro azygos shunt, which usually runs adjacent to it [ 31 ].…”
Section: Digestive Tractmentioning
confidence: 99%
“…The cardia, which is the cranial part of the stomach that is connected to the esophagus, lies on the left side of the midline [25] (Figure 7). The esophagogastric junction is an bifurcation of the diaphragm and the phrenoesophageal membrane [30]. The gastroesoph-ageal junction is also surgically important during the localization of the gastro azygos shunt, which usually runs adjacent to it [31].…”
Section: Stomachmentioning
confidence: 99%